FEATURES APPLICATION PROCEDURES MRB AVIONICS EQUIPMENT - A. I. Logvin; D. B. Rychenkov (Научный вестник МГТУ ГА)
The article discusses the selection of functionally important elements of the electronic equipment aircrafts.